Crystal structure analysis of Nd-doped ceria solid solutions - Matović B.; Dukić J.; Devečerski A.; Bošković S.; Ninić M.; Dohčević-Mitrović Z. (Science of Sintering, 2008)
This paper deals with Nd-doped ceria solid solutions: Ce1-xNdxO2-d with "x" ranging from 0 to 0.25. Six different powders were synthesized by applying the method based on selfpropagating room temperature reaction (SPRT) between metallic nitrates and sodium hydroxide. The method is known to assure very precise stoichiometry of the final product in comparison with a tailored composition. Rietveld refinement was employed to get structural information on the synthesized powder. An increase of Nd ion concentration increases the unit cell parameters and average bond distances. We have shown that all obtained powders were solid solutions with a fluorite-type crystal structure and all powder particles were of nanometric size (about 3 nm).